2016
DOI: 10.1007/s00520-016-3520-8
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and disturbed sleep as predictors of cancer-related fatigue in breast cancer patients: a multicenter NCORP study

Abstract: Purpose Cancer-related fatigue (CRF) is a prevalent and distressing side effect of cancer and its treatment that remains inadequately understood and poorly managed. A better understanding of the factors contributing to CRF could result in more effective strategies for the prevention and treatment of CRF. The objectives of this study were to examine the prevalence, severity and potential predictors for the early onset of CRF after chemotherapy cycle 1 in breast cancer patients. Methods We report on a secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 40 publications
5
35
1
3
Order By: Relevance
“…Most demographical characteristics-marital status, cohabitation, employment, physical activity and daily help-were not significantly related to CRF. Young age was associated with increased levels of fatigue in some research, 23 but we found the contrary in the reduced motivation dimension. Another study supported our findings, showing that older adults, whatever the type of cancer they had, reported more fatigue than did younger adults.…”
Section: Comparison With Literaturecontrasting
confidence: 82%
“…Most demographical characteristics-marital status, cohabitation, employment, physical activity and daily help-were not significantly related to CRF. Young age was associated with increased levels of fatigue in some research, 23 but we found the contrary in the reduced motivation dimension. Another study supported our findings, showing that older adults, whatever the type of cancer they had, reported more fatigue than did younger adults.…”
Section: Comparison With Literaturecontrasting
confidence: 82%
“…Additional studies of patients with cancers that occur across both genders (e.g., GI, lung) will allow for an evaluation of the independent contributions of gender and cancer diagnosis to evening fatigue severity. In prior reports,[5,9,46] the association between years of education and higher mean fatigue scores is inconsistent. Whether education is a proxy for some other demographic characteristic (e.g., socioeconomic status) warrants investigation in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cancer usually experience a cluster of symptoms, including sleep disturbance, fatigue, depression, and anxiety. 2 Sleep disturbance is closely correlated with cancer-related fatigue, 29 but pharmacological intervention in conventional medicine has clinical limitations in improving fatigue in patients with cancer or survivors of cancer with insomnia. 30 In our study, fatigue was alleviated in addition to sleep improvement.…”
Section: Discussionmentioning
confidence: 99%